2013
DOI: 10.1111/apt.12396
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining stable symptom control in inflammatory bowel disease: a retrospective analysis of adherence, medication switches and the risk of relapse

Abstract: SummaryBackground Maintenance therapy with 5-aminosalicylic acid (5-ASA) is a key strategy for preventing relapse in many patients with inflammatory bowel disease (IBD). Factors which disrupt 5–ASA delivery, such as non-adherence and 5-ASA switches, may destabilise symptom control.Aim To investigate the impact of non-adherence and medication switches on stable symptom control in UK patients with IBD.Methods A retrospective cohort study was conducted using a UK dispensing database. Adherence was analysed in ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 14 publications
0
28
1
2
Order By: Relevance
“…In the paper, 2 we state that the proxy measure is unvalidated, and agree that clinical data, which would accurately represent flare activity, would be desirable. However, this was not available, and we believe it was therefore valid to develop a proxy measure of flare.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…In the paper, 2 we state that the proxy measure is unvalidated, and agree that clinical data, which would accurately represent flare activity, would be desirable. However, this was not available, and we believe it was therefore valid to develop a proxy measure of flare.…”
mentioning
confidence: 82%
“…However, the sensitivity and specificity of the history and PPI response to diagnose GERD are mediocre. 1,2 As such, many with continued heartburn require a diagnostic work up that typically includes endoscopy and pH or impedance-pH studies, to differentiate refractory GERD 3 from functional heartburn (FH). Routine biopsies of the distal oesophagus to diagnose GERD are not recommended by the recent ACG guidelines.…”
mentioning
confidence: 99%
“…There was also a 60% reduction in hospital visits due to flare of disease, 45% reduction in family doctor visits and 50% reduction in steroid usage [53] . In addition, Motoya et al [54] reported a retrospective analysis of 46 patients with active ulcerative colitis, who were switched from a [55] found in a retrospective study that stable patients who switched mesalazine formulations had a 3.5 fold greater risk of relapse compared to those who did not switch. This indicates that the mesalazine formulations are not bioequivalent and disruptions to maintenance mesalazine should be avoided.…”
Section: Changing Mesalazine Formulationsmentioning
confidence: 99%
“…Non-adherence or disruption of maintenance therapy destabilizes disease activity, leading to exacerbations of symptoms, such as nausea, abdominal pain, fatigue, diarrhea, fistulae or abscesses (Robinson, Hankins, Wiseman, & Jones, 2013). In the long term, adherence to maintenance medications significantly reduces the risk of developing colorectal cancer by up to 75% in UC patients (Van et al, 2005).…”
Section: Preventing Relapses Complications and Morbiditiesmentioning
confidence: 99%
“…Achieving disease remission results in significant improvement of bowel symptoms, but also overall physical and psychosocial wellbeing. Exacerbations of clinical symptoms can be a source of psychological issues in adolescents (Robinson et al, 2013).…”
Section: Improving Physical and Psychosocial Wellbeingmentioning
confidence: 99%